The study of the vibration under different lubrication states based on Stribeck curve. (June 2022) - Yu, Haijie; Wei, Haijun
The tribology system is a complex nonlinear dynamical system. To study the vibration under different lubrication states, the experiments on full-film lubrication state and mixed lubrication state are designed based on Stribeck curve. In full-film lubrication state, vibration signal energy does not increase, but in mixed lubrication state, vibration signal energy increases with the increase of loading force. Under the condition of full-film lubrication, the autocorrelation function of vibration signal is similar to that of noise signal, which has smooth characteristics. In mixed lubrication state, the autocorrelation function of vibration signals has the characteristics of narrow convergence. Results reflect that for smaller loads there are no friction-induced vibrations due to full-film lubrication and for higher loads the friction-induced vibration comes into existence as the rough peaks between pin and disk surfaces come into play.